2022
DOI: 10.1002/fam.3109
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of molten bubble layer growth and bubble size distribution in post‐flame‐spread PMMA samples

Abstract: Although thermoplastics possess many desirable traits as solidified materials, they are combustible and burn readily. Post burning samples of polymethylmethacrylate (PMMA) are the focus of this study. During flame spread, PMMA forms a bubble containing molten surface layer that influences the spread rate and the surface mass efflux. This study examines the formation and distribution of bubbles inside a PMMA sample that has previously been subjected to flame spread and then re‐hardened into its solid state. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The same assumption was made by Linteris et al [14] to justify absorption coefficients measured at room temperature may vary when increasing temperature. Recently, Hossain et al showed that bubbling may also affect the flame spread rate by modifying the effective thermal conductivity of the condensed phase [26]. The authors determined the bubble size distribution in the molten zone after the flame spread.…”
Section: Al Proposed An Analytical Solution Formentioning
confidence: 99%
“…The same assumption was made by Linteris et al [14] to justify absorption coefficients measured at room temperature may vary when increasing temperature. Recently, Hossain et al showed that bubbling may also affect the flame spread rate by modifying the effective thermal conductivity of the condensed phase [26]. The authors determined the bubble size distribution in the molten zone after the flame spread.…”
Section: Al Proposed An Analytical Solution Formentioning
confidence: 99%